Long-Term Efficacy and Safety of Bimekizumab and Other Biologics in Moderate to Severe Plaque Psoriasis: Updated Systematic Literature Review and Network Meta-analysis - Richard B. Warren; Kerry Donnelly; Sandeep Kiri; Vanessa Taieb; Mahmoud Slim; Kyle Fahrbach; Binod Neupane; Marissa Betts; April Armstrong (Adis, Springer Healthcare, 2024)
Abstract Introduction Biologic treatments have made complete skin clearance in moderate to severe plaque psoriasis a real possibility. Although clinical trials demonstrated the superiority of bimekizumab over secukinumab, adalimumab, and ustekinumab, direct comparisons with other biologics are not available. This systematic literature review (SLR) and network meta-analysis (NMA) aimed to evaluate the 1-year efficacy and safety of bimekizumab versus other biologic systemic therapies for moderate to severe plaque psoriasis. Methods We conducted an SLR to retrieve published randomised controlled trials (RCTs) in patients with moderate to severe plaque psoriasis. We searched MEDLINE, Embase, the Cochrane Central Register of Controlled Trials and Cochrane Database of Systematic Reviews and PsycINFO on 13 January 2022. Two NMA types were used to analyse the long-term achievement of 100% improvement from baseline in Psoriasis Area and Severity Index (PASI 100): (1) NMA of cumulative clinical benefits, based on the area under the curve, from week 0 to 52; (2) multinomial NMA at weeks 44‒60. Binomial NMA was used to evaluate long-term serious adverse events (SAEs). Results The SLR identified 38 RCTs, of which 19 were included in the NMA. Bimekizumab 320 mg administered every 4 weeks to week 16 then every 8 weeks (Q4W/Q8W) showed a greater cumulative average number of days of PASI 100 response compared with all other biologics. These differences were statistically significant versus all biologics, except risankizumab 150 mg. The multinomial NMA demonstrated that interleukin (IL)-17 and IL-23 inhibitors were the most efficacious treatments. No significant differences were found in long-term occurrence of SAEs. Conclusion Bimekizumab 320 mg Q4W/Q8W was superior to most other treatments in maintaining complete skin clearance during the first year of treatment. It demonstrated a greater cumulative average number of days with completely clear skin while displaying a comparable safety profile compared with all other biologics.